2022
DOI: 10.36349/easjbg.2022.v04i01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of 𝛽-Lactamases and Extended Spectrum 𝛽-Lactamase Enzymes among Bacteria: A Threat to Effective Health Care Delivery

Abstract: Antibiotic discovery continue to play a critical role in disease containment. Misuse and overuse of these drugs are the main drivers in the development of drug resistant pathogens. The World Health Organisation has declared that Antimicrobial resistance is one of the top 10 global public health threats facing humanity. There is the fears that if nothing is done, it might end the antibiotic era soon. In 2017 alone, over 9000 human deaths were caused by ESBL-producing Enterobacteriaceae in the USA. The ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These variations in the occurrence of this enzyme may be because not all strains or species of these isolates are capable of producing Carbapenamases. More so, it may be because the test isolates are clinical isolates and not all patients harbored these categories of isolates that produce Carbapenamases [2]. The work of Yusuf T, et al [4], which report the first cases of the circulation of Carbapenemase isolates in Kano also revealed that carbapenemase-producing isolates are in circulation in different parts of Kano, at varying levels and locations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations in the occurrence of this enzyme may be because not all strains or species of these isolates are capable of producing Carbapenamases. More so, it may be because the test isolates are clinical isolates and not all patients harbored these categories of isolates that produce Carbapenamases [2]. The work of Yusuf T, et al [4], which report the first cases of the circulation of Carbapenemase isolates in Kano also revealed that carbapenemase-producing isolates are in circulation in different parts of Kano, at varying levels and locations.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes are diverse and are in rapid circulation throughout the world [1]. Their health burden is coupled with the fact that the antibiotics which it renders inactive, are the ones regarded as the last resort treatment option against all serious bacterial infections caused by both Gram positive and Gram negative organisms [2]. To date, these enzymes are known to be Rabiu produced by only Gram negative Enterobacteriaceae such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, and Acinetobacter baumannii among others [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation